A Morphological Study of Rakshani Dialect of Balochi - Bibi, Hanifa; Baloch, Hamid Ali (sourcecoder, 2024)
The Rakhshani dialect of Balochi is one of the major and widespread dialects of the Balochi language. It extends from south of Panjgur to the west of Kalat, from Kalat to Rod-e Hilmand in Afghanistan, and to the Záhidán and Saráwán areas of Iran. Although it has five sub-dialects, these sub-dialects share common morphological, honological, syntactic, and lexical structures. This paper illustrates the morphological structure of the Rakhshani dialect of the Balochi language.